Retrospective study on equine cases referred to University Veterinary Hospital (UVH), Universiti Putra Malaysia from year 2013 to 2017 - Mohamad Asharaf, Aziemah (2018)
An increase number of equine clinical cases reported to the University Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM) was observed. Therefore, a retrospective study was carried out in order to determine the prevalence of equine cases referred to UVH, UPM for the past five years as well as to identify different clinical problems in horses from different horse usage and management practice in relation to its occurrence rate. Data of equine clinical cases referred to UVH from year January 2013 to December 2017 were gathered and recorded. A total of 4,577 equine cases were recorded and analysed based on case number, horse establishment, type of work and clinical problems. The total of cases recorded in year 2013 including revisit cases was 877 (19.16%), year 2014 was 1,049 (22.92%), year 2015 was 1,026 (22.42%), year 2016 was 955 (20.86%) and year 2017 was 670 (14.64%). The highest cases reported involved the musculoskeletal (34.34 %), followed by traumatic injuries (14.57 %) and gastrointestinal tract problems(10.23 %). The data collected provide a valuable resource to investigate the post-operative management by horse owners.